2019
DOI: 10.1515/htmp-2019-0050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Solid Solution Temperatures on Microstructure and Mechanical Properties of the AA7075 Alloy After T6 Heat Treatment

Abstract: In this study, the effect of solid solution temperature on microstructure and mechanical properties of the AA7075 alloy after T6 heat treatment was investigated. Following solid solution at five different temperatures for 2 hours, the AA7075 alloy was quenched and then artificially aged at 120∘C for 24 hours. Hardness measurements, microstructure examinations (SEM+EDS, XRD) and tensile tests were carried out for the alloys. The results showed that the increased solid solution temperature led to formation of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The peaks appear only on specimens AA170 and AA195 because the quantitative proportion of the MgZn2 phase is higher due to higher aging temperature. The second peaks are most visible in the specimen aged at 195° C. Due to their small proportion and the overlapping of some peaks, the presence of the phases Al2CuMg (Sphase), Al6Mg11Zn11 (T-phase), Al7Cu2Fe, which are determined as insoluble impurityoriginated particles [30][31][32], and Al6Fe should be further verified by electron microscopy and microanalysis.…”
Section: Resultsmentioning
confidence: 92%
“…The peaks appear only on specimens AA170 and AA195 because the quantitative proportion of the MgZn2 phase is higher due to higher aging temperature. The second peaks are most visible in the specimen aged at 195° C. Due to their small proportion and the overlapping of some peaks, the presence of the phases Al2CuMg (Sphase), Al6Mg11Zn11 (T-phase), Al7Cu2Fe, which are determined as insoluble impurityoriginated particles [30][31][32], and Al6Fe should be further verified by electron microscopy and microanalysis.…”
Section: Resultsmentioning
confidence: 92%
“…Figure 6 illustrates the XRD results for the experimental test (A3B3C1) of the confirmation test, revealing prominent peaks corresponding to Al, ZrO 2 , MgSi, MgZn 2 , and Al 2 Cu [34]. The formation of secondary phases on the surface was found to enhance the composite's wear resistance and microhardness, with temperature playing a key role in promoting the formation of these secondary phases [35].…”
Section: Optimization Of Heating Process Parametersmentioning
confidence: 99%
“…It is suggested that the heat treatment process follows the sequence saturated solid solution → GP zones → ή (MgZn2) → η (MgZn2). The orthorombic S (Al2CuMg) phase and the T (Al32(Mg,Zn)49) phase may also form [11][12][13].…”
Section: Introductionmentioning
confidence: 99%